2016
DOI: 10.1093/gji/ggw188
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-source electromagnetic and seismic delineation of subseafloor fluid flow structures in a gas hydrate province, offshore Norway

Abstract: SUMMARYDeep sea pockmarks underlain by chimney-like or pipe structures that contain methane hydrate are abundant along the Norwegian continental margin. In such hydrate provinces the interaction between hydrate formation and fluid flow has significance for benthic ecosystems and possibly climate change. The Nyegga region, situated on the western Norwegian continental slope, is characterized by an extensive pockmark field known to accommodate substantial methane gas hydrate deposits. The aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…Based on their high resistivities, Edwards [1997] suggested the use of time domain CSEM data for the detection of submarine gas hydrates. Several gas hydrate exploration case studies followed using CSEM systems in time domain [Yuan and Edwards, 2000;Schwalenberg et al, 2005Schwalenberg et al, , 2010aSchwalenberg et al, , 2010b, frequency domain [Weitemeyer et al, 2006[Weitemeyer et al, , 2011Weitemeyer and Constable, 2010;Ellis et al, 2008;Constable et al, 2016;Goswami et al, 2015, Attias et al, 2016, and a DC resistivity system [Goto et al, 2008].…”
Section: Methodsmentioning
confidence: 99%
“…Based on their high resistivities, Edwards [1997] suggested the use of time domain CSEM data for the detection of submarine gas hydrates. Several gas hydrate exploration case studies followed using CSEM systems in time domain [Yuan and Edwards, 2000;Schwalenberg et al, 2005Schwalenberg et al, , 2010aSchwalenberg et al, , 2010b, frequency domain [Weitemeyer et al, 2006[Weitemeyer et al, , 2011Weitemeyer and Constable, 2010;Ellis et al, 2008;Constable et al, 2016;Goswami et al, 2015, Attias et al, 2016, and a DC resistivity system [Goto et al, 2008].…”
Section: Methodsmentioning
confidence: 99%
“…Notable insights have been gained from laboratory studies to date (e.g., Handa, 1990;Kerkar et al, 2014;Priegnitz et al, 2015;Priest et al, 2009;Tohidi et al, 2001), but further research is needed into the following areas: (i) the causes of the commonly observed discrepancy between hydrate saturation estimates from seismo-acoustic and electrical resistivity methods (Attias et al, 2016;Goswami et al, 2015;Lee & Collett, 2006;Miyakawa et al, 2014;Sahoo et al, 2018) (referred to here as the seismicelectrical discrepancy); and (ii) the effect of methane hydrate saturation and its spatial distribution in the host sediment on the seismo-acoustic velocity of hydrate-bearing sediments. Some studies associate the seismic-electrical discrepancy to the coexistence of gas and hydrate, as the presence of gas can reduce the seismic velocity but not the electrical resistivity of the sediment (e.g., Goswami et al, 2015;Lee & Collett, 2006;Miyakawa et al, 2014;Sahoo et al, 2018).…”
Section: 1029/2018gc007710mentioning
confidence: 99%
“… Note . References: 1, Schnurle et al (); 2, Hsu et al (); 3, Fohrmann and Pecher (); 4, Schwalenberg et al (); 5, Lee and Collett (); 6, Miyakawa et al (); 7, Attias et al (); 8, Plaza‐Faverola et al (); 9, Goswami et al (); 10, Hustoft et al ().…”
Section: Introductionmentioning
confidence: 99%